American foreign policy after 9/11 : a strategic turn towards unilateralism. - Seow, Troy Kim Cheng. (2008)
The Bush administration's foreign policy represents a distinct strategic turn towards unilateralism, due to these factors: (1) American economic and military power (2) Psychological impact of the Al-Qaeda attacks on Sept 11, 2001 (3) The belief that in order to achieve its security, America needs to be free from the international rules, and also use military strength to reshape the world.